Quality Evaluation Model of Information Reconstruction via Electromagnetic Emanation - Zidong Zhang; yuanhui Yu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Electromagnetic emanations from IT device may leak information they process. By analyzing the characteristics of electromagnetic emanations, eavesdropper could reconstruct critical information. Particularly information displayed on monitor faces a serious security risk. Although various electromagnetic information leakage countermeasures have been proposed try to solve the information security problems, their effectiveness evaluations are mostly subjective. The comparison of their efficiency and the evaluation of information reconstruction implementations are challenging issues, no reliable quantitative metric available. From the information theory point of view, this paper presents an evaluation model for assessing monitor information reconstruction through electromagnetic emanations. By a reconstruction experiment, the amount of information leakage and information reconstruction is implemented and analyzed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4467